Aplicación de un Sistema de Contabilidad de Costos por Procesos en el cultivo del arroz para mejorar el rendimiento de la cosecha de los agricultores individuales de Chepén. - Palomino Correa, Martin Edwin (2014)
This research project intends to present a study by implementing a design for Cost Accounting processes for better management in rice cultivation conducted by individual farmers in the Irrigation Commission Chepén. Since rice cultivation uses and they do so by inherited customs (traditional) without any criteria and application procedures for Process Cost Accounting; so that the non-presence of CP in this agricultural activity generates empirically that farmers in the Irrigation Commission Chepén and even Regional and National; conduct their activities improperly determining performance: Loss or Gain in every agricultural campaign The work is divided into three main sections where first will address the qualitative aspects, ie know the processes or cultural practices in the planting of rice, for a design accounting agricultural costs establish a best designs for determining the costing and profitability or profit or loss in every agricultural campaign . The added value of this research emphasizes that adequately and accurately in each production process of rice accounts for its determined and costing, as the sample used was determined design cost accounting processes instructing farmers to be able to determine quantitatively and qualitative activities and tasks; reaching set as a result of research that the gain obtained by the individual farmer Chepén is 34% based on the total 100% of Production Costs for 1 Hectare Rice and therefore recommends that farmers should apply systems costs and change processes conventional or traditional rice cultivation which will allow them to achieve a gain of 34% happen to get a 44% to 50% methods. As a result of the investigation and in accordance with the objectives of this thesis research with the objectives which is demonstrated in the results, discussion, conclusion and recommendation was made.